2006
DOI: 10.3892/or.16.4.885
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and antiangiogenic activity of soy isoflavone genistein in mouse models of melanoma and breast cancer

Abstract: Tumor invasion, angiogenesis and metastasis involve secretion of proteolytic enzymes and cell migration into blood vessels. Tumor cells are capable of degrading the extracellular matrix via a proteolytic cascade that includes urokinase-type plasminogen activator (uPA) and matrix metalloproteases (MMPs). We have investigated the antitumor and antiangiogenic properties of soy isoflavone genistein in B16 melanoma and F3II mammary carcinoma mouse models. At non-cytotoxic concentrations (0.1-50 μM) genistein induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 29 publications
7
80
0
1
Order By: Relevance
“…However, matrix degradation by MMPs can alter the basic processes of cell proliferation and apoptosis. The chemopreventive effect of the flavonoids, flavonols (quercetin and kaempferol) and isofl avones (genistein, genistin and daidzein) has been observed through the suppression of cell proliferation [35] , inhibition of angiogenesis [36] , inhibition of invasion [37] and stimulation of apoptosis in breast carcinoma cells [38] . The inhibition of invasion of cancer cells is of great significance in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, matrix degradation by MMPs can alter the basic processes of cell proliferation and apoptosis. The chemopreventive effect of the flavonoids, flavonols (quercetin and kaempferol) and isofl avones (genistein, genistin and daidzein) has been observed through the suppression of cell proliferation [35] , inhibition of angiogenesis [36] , inhibition of invasion [37] and stimulation of apoptosis in breast carcinoma cells [38] . The inhibition of invasion of cancer cells is of great significance in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that genistein can inhibit the growth of various hormone-responsive cancer cell lines, such as breast and prostate, both in vitro and in vivo (12)(13)(14)(15). The anticancer effects of genistein have been ascribed to several signaling pathways and mechanisms that lead to cell cycle arrest, apoptosis, invasion, metastasis, and angiogenesis, attributes that could potentially prevent tumor initiation and progression (9,13).…”
Section: Introductionmentioning
confidence: 99%
“…With the challenge of finding new drugs which could inhibit VM, the soybeans isoflavone called genistein was proposed. This molecule was found to be able to inhibit VM formation of uveal melanoma through down-regulation of VE-cadherin in vitro [27,28]. In another study Itzhaki et al tested the ability of nicotinamide to inhibit VM activity in melanoma cells [29].…”
Section: Discussionmentioning
confidence: 99%